Correlation of BUB1 and BUB1B with the development and prognosis of endometrial cancer - Zhang, Huicong; li, yuhao; Lu, Huixia (Scientific reports, 2024)
This study aimed to evaluate the expression and clinical significance of budding uninhibited by benzimidazole 1 (BUB1) and BUB1 mitotic checkpoint serine/threonine kinase B (BUB1B) in endometrial carcinoma (EC). BUB1 and BUBIB expressions were evaluated by bioinformatics. Protein expression, clinical features, prognosis and immune cell infiltration were explored in 20 EC tumors. siRNA was used to evaluate BUB1 and BUBIB function in EC cells. BUB1 and BUBIB were highly expressed in 26 cancers. BUB1 was associated with overall survival (OS) in eight cancers and disease-free survival in ten; BUB1B was associated with OS in nine cancers and DFS in eleven. BUB1 and BUBIB exhibited high frequencies of gene changes (mainly mutations, > 5%) in cancer. BUB1 was negatively correlated and BUB1B was positively correlated with cancer-associated fibroblasts and endothelial cell infiltration. BUB1 and BUBIB knockdown decreased migration and invasion in EC cells. High BUB1 expression correlated with tumor malignant phenotypes ( P < 0.05). High BUB1 mRNA expression reduced OS ( P = 0.00036) and recurrence-free survival ( P = 0.0011). High BUB1B mRNA expression reduced OS ( P = 0.0024). BUB1/BUB1B correlated with activated CD8 + T and CD4 + T cell infiltration. BUB1 and BUBIB are highly expressed and correlated with clinicopathological characteristics in EC. BUB1 and BUBIB are potential prognosis markers and immunotherapy targets.